Development of an expert system for mechanical design of pressure vessels / Nor Hazelah Kasmuri - Kasmuri, Nor Hazelah (2008)
An expert system for mechanical design of a pressure vessel, known as DePV, was developed in this study. Expert system is a branch of Artificial Intelligence that can replace the role of human expert in form of knowledge based system. There are two methods involved, namely object - oriented programming and rule based programming. Object - oriented programming is a composition of data structure which is called an object. While, rule based programming comprises forward and backward chaining. KAPPA PC® expert system shell is used as a tool to develop this prototype software. It supports the conceptual mechanical design procedure as stipulated in the American Society of Mechanical Engineers (ASME) Boiler & Pressure Vessel Design Code: Division 1 from the initial to final design stages. For stress analysis purposes, British Standard (BS5500) Design Code is chosen over ASME because design approach is simple and can obtain accuracy of the results. The expert system methodology used facilitates the development of DePV which consists of knowledge acquisition, knowledge based construction and prototype implementation. The study rationalized the design procedure and the factors affecting the pressure vessel design such as the design pressure (either internal or external), temperature, shell thickness, selection of materials of construction, stress analysis procedure, its supports and ancillary items. The hierarchy of the mechanical design was developed in the form of a schematic flow diagram. The data for process designs, formulation and case studies were first input into DePV. One can then obtain information and results on which series of design units will be calculated, selection of design pressure for vessel will be considered as well as for the stress analysis. The realization of this study will improve the database design of the pressure vessel system for petrochemical industries.